Resting energy expenditure in professional dancers as an objective measure of low energy expenditure - Wyon, M.; Allen, N.; Brown-Appenzeller, Coack, R.; Devonport, T.; Gregory, K.; Penner, J.; Hassan-Smith, Z.; Webster, R.; Wolman, R. (BMJ Open Sport & Exercise Medicine, 2026)
Objective To investigate the prevalence of low resting energy expenditure (REE) in ballet dancers and to examine its association with low energy availability (LEA) questionnaires and physiological parameters, including menstrual function and body composition.